Our first foreign war the impact of the South African War 1899-1902 on New Zealand - Robson, Nigel (Massey University Press, 2021)
Foreshadowing our unseemly haste to fight for King and Country in 1914, New Zealanders were enthusiastic supporters of the colonial war between Britainand the Boers when it was declared in 1899. The country welcomed the chance to prove itself and its loyalty to the British Empire on an international stage
Keywords: Burenkrieg; Auswirkung; Neuseeland; New Zealand / Army / History / 19th century; New Zealand / Army / History / 20th century; South African War, 1899-1902 / Participation, New Zealand; South African War, 1899-19902 / Participation, New Zealand / Biography; New Zealand / History / 19th century; New Zealand / History / 20th century; New Zealand / Biography; New Zealand - Biography; New Zealand / Army; New Zealand; Pakanga; Hōia; Kōrero nehe; 1800-1999; Biographies; History